Developing Digital Platform of The Askin Application Using House of Quality - Yudha Heryawan Asnawi; Naura Rahmalia; Suhendi (Business Review and Case Studies, 2021)
Healthcare is the need of many people to fulfill their lifestyles. The desire to achieve maximum appearance encourages everyone to the healthcare of skin. The relatively high cost and the low number of aesthetic doctors in certain areas have led some people to do facial treatments independently using skincare products. Askin's business idea in the form of a facial care application is one of the solutions to help users with facial skincare. This research aims to analyze the problem factors of skincare users in carrying out facial skincare, analyze the right solution, and design a Minimum Viable Product that suits the Askin application. This research was conducted from December 2020 to January 2021 using the House of Quality research method to identify the best features. This research also used female research respondents aged 19-34 years using skincare products and domiciled in the City of Bukit Tinggi as a sample of this study. The results of this research contained six problems from skincare users, which is not knowing the type/condition of the skin in detail, not knowing the right skin care product to use, experiencing an incompatibility when using skincare products, difficulty obtaining skincare products, having no place to ask and consult, and not using skin care regularly. In conclusion, the Askin Application has ten application features formulated based on consumer needs and desires. These features are implemented in the minimum viable product of the Askin application. Keywords: business development, digital platform, facial care, house of quality